A generalized electromechanical coupled model of standing-wave linear ultrasonic motors and its nonlinear version. (1st March 2023) - Li, Xiang; Guo, PengTao; Ding, Yuan; Chen, Zhiwei; Wang, Xu; Lv, Qibao
Highlights: A generalized electromechanical coupled model is proposed for linear ultrasonic motors. The model provides sufficient information on the electrical and mechanical characteristics. An extensional model considering nonlinear vibration is presented and discussed. Abstract: For the systematization of research on standing-wave linear ultrasonic motors (SWLUMs), this work develops a generalized electromechanical coupled model for characterizing SWLUMs. The proposed model focuses on dealing with modeling the generalized two-stage energy conversion in SWLUMs. The first-stage energy conversion is modeled by a four-terminal equivalent circuit model, which with a phase shifter and a couple of electromechanical transformers based on the electromechanical analogy method. The second-stage energy conversion is modeled by a physics-based, friction-driven system, involving contact nonlinearities between the stator and the mover. Furthermore, the effectiveness of this model and its further extension considering nonlinear vibrations of piezoelectric transducer (stator) are exemplified and discussed by a classical SWLUM with V-configuration stator, thereby indicating that the presented generalized model is valuable and pragmatic in simulating and characterizing SWLUMs both in electrical and mechanical domains.